Applying the Ottawa subarachnoid haemorrhage rule on a cohort of emergency department patients with headache. (December 2018) - Chu, Kevin H.; Keijzers, Gerben; Furyk, Jeremy S.; Eley, Robert M.; Kinnear, Frances B.; Thom, Ogilvie N.; Howell, Tegwen E.; Mahmoud, Ibrahim; Ting, Joseph Y.S.; Brown, Anthony F.T.
Abstract : Objective: The Ottawa subarachnoid haemorrhage (SAH) rule suggests that alert patients older than 15 years with a severe nontraumatic headache reaching maximum intensity within 1 h and absence of high-risk variables effectively have a SAH ruled out. We aimed to determine the proportion of emergency department (ED) patients with any headache fulfilling the entry criteria for the Ottawa SAH rule. Patients and methods: The Ottawa SAH rule was applied retrospectively in a substudy of a prospective snapshot of 34 EDs in Queensland, Australia, carried out over 4 weeks in September 2014. Patient aged 18 years and older with a nontraumatic headache of any potential cause were included. Clinical data and results of investigations were collected. Results: Data were available for 644 (76%) patients. A total of 149 (23.1%, 95% confidence interval: 20.0–26.5%) fulfilled and 495 (76.9%, 95% confidence interval: 73.5–80.0%) did not fulfil the entry criteria. In patients who fulfilled the entry criteria, 30 (<5% overall) did not have any high-risk variables for SAH. In patients who fulfilled the entry criteria and had at least 1 high-risk feature, almost half (46%) received a computed tomographic brain. No SAH were missed. Conclusion: In this descriptive observational study, the majority of ED patients presenting with a headache did not fulfil the entry criteria for the Ottawa SAH rule. Less than 5% of the patients in this cohort could have SAH excluded on the basis of the rule. More definitive studies are needed to determine an accepted benchmark for the proportion of patients receiving further work-up (computed tomographic brain) after fulfilling the entry criteria for the Ottawa SAH rule.